PELATIHAN KELOMPOK PETANI HOLTIKULTURA DALAM PENINGKATAN LAJU PERTUMBUHAN DAN PRODUKTIVITAS HASIL PANEN DENGAN MEMANFAATKAN TEKNOLOGI AUDIO ORGANIC GROWTH SYSTEM (AOGS) - Kadarisman, Nur; Purwanto, Agus; Rosana, Dadan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Based on the result of Grand Competition and National Strategic research, a result is obtained the field of modification and engineering of audio technology (AOGS; Audio Organic Growth System) unifying foliar and audio intensity variable optimization, which are optimum frequency and intensity to increase productivity and quality of plants which is in accordance with the effort to increase food resilience. This result is definitely very useful to food plant farmers to increase their crop productivity, such that in this community service the activities will be done with some objectives, viz.: (1) introduce the AOGS technology device which uses local insects (garengpung and jangkring, kinjengtangis) as sound sources and also how to operate it; (2) increasing plant productivity (chilli, ground peanut, and onion) which is managed by farmers through application of AOGS technology; and (3) increasing synergic cooperation between farmers and the university. The activities of this community service are done in the framework of workshop starting from introducing SC-AOGS technology, using SC-AOGS device, and through field tests. The achievement indicators of this excellence community service, can be observed from several aspects, including (1) the number of farmers that participate in the workshop is quite a lot and is the target to spread throughout the technology resulted from this community service;(2) the crop harvested turns out to increase such that has an impact on the income of farmers; (3) from the process itself, the involvement of farmers are enthusiastic and spirited. Important events which are observed throughout the activity are (1) AOGS technology initially introduced is considered not known by participants, but after some explanations they understand that this technology is very simple, natural, and environment friendly, and can be easily reproduce by farmers in Kricaan Mesir village, Salam, Magelang District; (2) the participants look enthusiastic with the workshop topics, in the discussion, and actively trying the AOGS device; and also (3) participants are trained to construct and use AOGS and describe implementation plan, which is then given guidance and the device to use